PENGARUH ASAL BENIH TIMOHO (Kleinhovia hospita L) TERHADAP PERTUMBUHAN BIBIT DI TINGKAT PERSEMAIAN - Rafelinta Daradwinta; Ragil Pinasti; Lukman Hakim (Jurnal Pemuliaan Tanaman Hutan, 2020)
Timoho (Kleinhovia hospita) wood is one of the raw materials for keris sheath that having high aesthetic and economic values. Due to exploitation of keris raw material that outmatches its planting activities, this type of tree is already hard to find in the Special Region of Yogyakarta, so this research aims to determine the generative propagation techniques carried out in the nursery of Center for Forest Biotechnology and Tree Improvement. Genetic material in the form of seeds in this study came from the parent trees grown in Bulaksumur region and Purwobinangun region, Yogyakarta. The methods that will be used are sampling, seed extraction, seed scarification in hot water for 24 hours, germination using wet tissue as media in petri dish, and planted in polybags. The result showed that viability of seeds from Bulaksumur region was 80% while that from Purwobinangun region was 68%. Observation and measurement of stem length and number of leaves every 2 weeks for 42 days showed that the number of timoho seed leaves from Purwobinangun had a higher number of leaves and a longer stem length, which is 19,11 ± 2,66 leaf blade and 11,54 ± 2,77 cm than the number of leaves and stem length from Bulaksumur, which is 0,59 ± 1,07 leaf blade and 7,59 ± 1,17 cm. Based on this research, it was concluded that although the viability of seeds from Bulaksumur was higher, the possibility of inbreeding from it broodstock caused the growth of seeds from Bulaksumur not as good as the growth of seeds from Purwobinangun